The effects of starter cultures and plant extracts on the biogenic amine accumulation in traditional Chinese smoked horsemeat sausages. (April 2015) - Lu, Shiling; Ji, Hua; Wang, Qingling; Li, Baokun; Li, Kaixiong; Xu, Chengjian; Jiang, Caihong
Abstract: This study assessed the effects of starter cultures ( Lactobacillus sakei and Staphylococcus xylosus ) and plant extracts (tea polyphenols and essential oils of cinnamon, cloves, ginger, and anise) on the accumulation of biogenic amines in traditional Chinese smoked horsemeat sausage. Relative parameters such as microbiological growth, pH and aw were also evaluated. The results revealed that plant extracts and starter cultures suppressed the growth of pathogenic bacteria based on traditional microbiological methods and PCR-DGGE analyses. Additionally, the plant extracts and starter cultures reduced tryptamine, putrescine, cadaverine, histamine, and tyramine during ripening and storage. The inhibitory effects of the plant extracts were stronger than those of the starter cultures. There were synergistic effects between the plant extracts and starter cultures against the accumulation of biogenic amines and the growth of Enterobacteria. Essential spice oils, tea polyphenols, and amine-negative starter cultures should be added in the production of traditional Chinese smoked horsemeat sausage. Highlights: Effect of starter culture and compound plant extract on biogenic amines was studied. Both biogenic amines and the microbial ecosystem were investigated. Biogenic amines and Enterobacteria were inhibited synergistically. The starter culture and plant extract should be added in smoked horsemeat sausage.